DNA Barcoding for the Identification of Swim Bladders: An Approach to International Trade Monitoring - Freitas, Gabriela Idaline de [UNESP]; Rodrigues, Carlos E.; de Carvalho, Daniel Eduardo Visciano; Utsunomia, Ricardo [UNESP]; Porto-Foresti, Fabio [UNESP] (Elsevier, 2025)
The rapidly expanding global trade in fish maw (dried swim bladders) necessitates urgent forensic monitoring, as this highly processed commodity is morphologically unidentifiable, directly facilitating the illicit inclusion of vulnerable species in the legal supply chain. This research applied DNA Barcoding (cytochrome oxidase I; COI gene) to 120 fish maw samples seized by Brazilian environmental authorities at a major international airport to provide species-level identification and crucial data on trade practices. We identified eight species, with the overwhelming majority belonging to Amazonian Sciaenids (Cynoscion acoupa and Plagioscion auratus) and the catfish Sciades parkeri. Crucially, the definitive identification of C. acoupa and S. parkeri confirms the direct exploitation of species listed as Vulnerable by the IUCN, tracing their flow from multiple Brazilian states to major global consumer hubs, including Hong Kong, the United States, United Kingdom and China. Furthermore, the study exposed a critical methodological constraint: an initial ambiguous species assignment by the BOLD system (94% match) was only resolved by confirming the correct species, S. parkeri, through the NCBI database (100% match). This finding demonstrates the essential need for critical evaluation and the utilization of complementary reference libraries to overcome 'code gaps' in forensic analyses. These data underscore the essential role of molecular techniques as an enforcement tool for traceability and provide unequivocal evidence supporting the immediate need for targeted legislation and rigorous regulatory oversight to protect vulnerable Amazonian stocks.